2010
DOI: 10.1002/dc.21414
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated apocrine papillary carcinoma of the breast: Case report with clinicopathologic and immunohistochemical study

Abstract: We describe a case of encapsulated papillary carcinoma (EPC), apocrine variant in a 50-year-old woman. The patient presented a cystic lesion in her right breast, measuring 8 cm in diameter, containing three solid papillary nodules. A fine-needle aspiration showed isolated apocrine cells containing round nuclei, irregular nuclear membranes, fine chromatin, and prominent macronucleoli. The lesion was excised and showed a pure papillary apocrine carcinoma, which stained diffusely with GCDFP-15 and androgen recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Laforga et al [3] reported a case with an apocrine type of EPC, and described that their case showed features fitting with low-grade carcinoma according to the criteria of O'Malley and Bane [6], such as cell size, atypical nuclei with macronucleoli, architecture showing papillary and cribriform patterns of growth, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Laforga et al [3] reported a case with an apocrine type of EPC, and described that their case showed features fitting with low-grade carcinoma according to the criteria of O'Malley and Bane [6], such as cell size, atypical nuclei with macronucleoli, architecture showing papillary and cribriform patterns of growth, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…We think that encapsulated and solid papillary carcinomas, which lack myoepithelial cells, do not represent in situ carcinomas; however, they do not fall into the category of frank invasive carcinomas either. We think that encapsulated and solid papillary carcinomas represent an intermediate link between DCIS and frank invasive ductal carcinoma and certainly should not be over treated [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Apocrine changes of lesions of the breast can be seen in a spectrum from microscopic cysts to invasive carcinomas. [25] Preoperatively, apocrine carcinoma needs to be distinguished from benign apocrine lesions and granular cell tumor. [6] FNAC smears in benign apocrine lesions, such as atypical apocrine adenosis, apocrine adenoma, granular apocrine metaplasia and degenerative cysts are of low cellularity and are composed of cells arranged in flat more regular sheets.…”
Section: Discussionmentioning
confidence: 99%